Internet of things (IoT) based traffic management & routing solution for parking space - Zulnazim Dzulkurnain; Abd Kadir Mahamad; Sharifah Saon; Mohd Anuaruddin Ahmadon; Shingo Yamaguchi (Institute of Advanced Engineering and Science, 2019)
The idea of Internet of Things (IoT) based traffic management & routing solution for parking space is due to the vehicle parking has become major issue in urban areas. The growing number of vehicles has contributed to the traffic problem and vehicle parking issue nowadays. The main purpose of this project is to assist the user to locate the vacant parking space, which help to reduce time and fuel consumption on searching the parking space. This proposed system was used online system via website application, which assist people to find the available parking slot. In fact, the system counted the capacity of the available parking space and notified the user through the website application. Frankly, the system was equipped with an ultrasonic sensor, which acts as the detector that sent data to the microcontroller in order to update into UBIDOTS cloud server for data logger purposes. This system could lessen or solve the time management problem at the parking area, which user could save their time by checking the available parking slots in advance through the website application.